Social integration, community's sense of perception of safety among neighborhood communities in Klang Valley area - Che Saari, Nur Asiyah; Wan Jaffar, Wan Munira; Ahmad, Nobaya (Human Resource Management Academic Research Society, 2022)
Perception of safety has become a concerning issue in Malaysia. It is proven by the rapid growth of gated community in Malaysia due to public concern over the safety of their family. The important of the topic is to find out in what extent the social capital such as concept of social cohesion and sense of community besides environment design in helping to create perception on safety among residential community area in Klang Valley. The aim of this study was to determine the relationships between social cohesion, sense of community towards safety perception in Klang valley area community. The methodology was uses a quantitative approach and survey techniques using descriptive and inferential analysis. A total of 500 respondents covering gated and non-gated neighborhood communities in the Klang Valley area. Respondents were selected through multi-stage sampling method. Data were collected using a self -administered questionnaire form by the respondents with minimal monitoring by the researcher. A set of questionnaires that includes a combination of several scales were used, namely demographic background, social cohesion, sense of community and safety perception. Analysis was used is descriptive analysis, Pearson correlation and multiple regression. Major finding of the study is respondents who have better sense of community will create a better perception of safety in gated and non-gated resident. It is believed that the findings of this study would add new perspective on how social cohesion is important to create better perception of safety to their neighborhood community. Therefore, responsible parties such as local authorities need to give more emphasis to programs that build social capital among residents and eventually create a safe environment in a neighborhood. For further research, researcher can include environmental design as a second variable in strengthen social capital (sense of cohesion and sense of community) to build good vibe of perception of safety among gated and non-gated communities in Malaysia.